IoT SOLUTION FOR LEVEL MEASUREMENT IN THE OIL AND GAS INDUSTRY - Constantin Octavian Bercea (Romanian Journal of Petroleum & Gas Technology)
The fundamental goal of this work is to investigate and explore the design and construction methods for an intelligent, adaptable and flexible level measurement system, based on IoT (Internet of Things) technology. This automatic data acquisition, transmission and processing system must allow the level of a substance to be measured in a non-intrusive manner. The system also ensures safe operation for personnel servicing the monitored process and allows customization of the presentation of data sets, in a variety of formats, with maximum relevance to the user. The level measurement system proposed in the paper bases its operation on the characteristics of ultrasonic sensors. The intelligent modules of the system process, based on software algorithms, the data from the sensors and communicate them to other microprocessor subsystems for conversions, storage and presentation of the results. This intelligent level measurement system uses two sensor subsystems, with different degrees of complexity, to monitor two reservoirs in a park. These subsystems communicate permanently with a central control unit, the CCU, which collects and processes in real time the data transmitted to it in a WiFi LAN. In order to increase the degree of adaptability of the intelligent system to the measurement needs, it is possible to resort to increasing the number of sensors, placed in various locations, in a park of tanks for the storage of petroleum products.